Campylobacter in Raw Chicken Meat at Retail Level: Quantitative and Qualitative Assessment, Genomic Profiling, and Comparison With Isolates From Human Infections - Lucien Kelbert; Karen Barmettler; Jule Anna Horlbog; Marc J.A. Stevens; Nicole Cernela; Magdalena Nüesch-Inderbinen; Roger Stephan (Journal of Food Protection)
Campylobacter is the leading cause of human bacterial diarrheal disease, and the handling and consumption of poultry meat products account for most cases. This cross-sectional study aimed to determine the prevalence and levels of Campylobacter in Swiss and imported retail chicken meat during May – August 2024. Whole-genome sequencing (WGS) was applied to assess phylogenetic relatedness between Campylobacter from chicken meat samples and human infections occurring during the study time in Switzerland, and to identify antimicrobial resistance and virulence genes. A total of 300 different chilled or frozen chicken meat samples and 50 chilled marinated meat samples were analyzed by qualitative (enrichment) and quantitative (plating) ISO 10272-1:2017 and ISO 10272-2:2017 methods. After enrichment, the Campylobacter recovery rate was higher in chilled (62%) than in marinated meat (40%) or frozen chicken meat (11%). Campylobacter were more prevalent in meat from organically labeled meat (72%) and free-range labeled meat (77%) compared to meat with other labels. Quantitatively, 3.7% of chilled, nonmarinated meat had >100 colony-forming units (cfu)/g (range 100–700 cfu/g). The detection of multiple genetically indistinguishable isolates from meat and from humans indicated that chilled chicken meat is a major infection source for Swiss cases of campylobacteriosis. Antimicrobial resistance determinants included blaOXA, tet(O), and the T86I substitution in GyrA. Virulence genes cstIII, neuABC, wlaN, and cdtABC which are linked to the Guillain-Barré syndrome and gastrointestinal cancers, respectively, were identified. Our data highlight the need to reduce the levels of Campylobacter in chicken meat to protect public health. Freezing meat prior to retailing is an effective and relatively inexpensive measure to increase product safety and to reduce the risk of campylobacteriosis in humans.